1992
DOI: 10.1093/clinchem/38.3.394
|View full text |Cite
|
Sign up to set email alerts
|

Laser Immunonephelometry Reference Intervals for Eight Serum Proteins in Healthy Children

Abstract: Eight serum proteins were analyzed with the Behring nephelometer in samples from 479 healthy French children, ages three to 16 years. Girls had higher concentrations of IgM and albumin than boys had. Age appeared to be a main factor of variation for the proteins tested. Reference intervals are presented for IgG, IgA, IgM, albumin, transthyretin (prealbumin), retinol-binding protein, alpha 1-acid glycoprotein, and C-reactive protein. The significance of increased concentrations of C-reactive protein within a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Two studies did not include age (8,18). The remaining 15 studies (5)(6)(7)28,42,46,49,52,56,61,69,70,73,83,101) were considered acceptable for transthyretin measurements.…”
Section: Number Of Studies Available For Analysismentioning
confidence: 99%
“…Two studies did not include age (8,18). The remaining 15 studies (5)(6)(7)28,42,46,49,52,56,61,69,70,73,83,101) were considered acceptable for transthyretin measurements.…”
Section: Number Of Studies Available For Analysismentioning
confidence: 99%
“…Of the 30 studies included in these analyses, 11 (11,13,22,26,37,41,45,52,53,56,63) did not provide racial or ethnic information, 16 were mainly Caucasian (4)(5)(6)14,21,(23)(24)(25)(30)(31)(32)36,40,51,57,58), one consisted mainly of black Africans (48), and two consisted of Asians (19,20). There was insufficient data to determine whether racial or ethnic differences exist.…”
Section: Ethnic Group-specific Reference Rangesmentioning
confidence: 99%
“…The remaining 16 studies (4-6,13,14,19,21,23,24,30-32,36,48,51,57) provided acceptable central estimates. Of these, 12 also provided acceptable reference ranges(4)(5)(6)19,21,24,(30)(31)(32)36,48,51).…”
mentioning
confidence: 97%
“…A total of 34 publications were identified that contained information on α 1 -acid glycoprotein in apparently healthy individuals (4)(5)(6)(13)(14)(15)(16)(17)(18)(19)21,23,24,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)43,44,47,48,51,55,57,(59)(60)(61)(62). Eleven studies did not include adequate data on either reference material or assay methodology (18,28,34,35,44,47,55,(59)(60)(61)(62).…”
Section: Number Of Studies Available For Analysismentioning
confidence: 99%
“…Of the 30 studies included in these analyses, 11 (11,13,22,26,37,41,45,52,53,56,63) did not provide racial or ethnic information, 16 were mainly Caucasian (4)(5)(6)14,21,(23)(24)(25)(30)(31)(32)36,40,51,57,58), one consisted mainly of black Africans (48), and two consisted of Asians (19,20). There was insufficient data to determine whether racial or ethnic differences exist.…”
Section: Ethnic Group-specific Reference Rangesmentioning
confidence: 99%